Pemberdayaan Keluarga dalam Pendampingan Minum Obat Pasien Tuberkulosis Paru di Wilayah Pesisir Kecamatan Soropia - Sitti Rachmi Misbah; Lena Atoy; Muhaimin Saranani; Nurfantri Nurfantri; Dewi Sartiya Rini (Jurnal Inovasi, Pemberdayaan dan Pengabdian Masyarakat, 2021)
The family is the closest person who has an important role in the treatment of pulmonary tuberculosis. The treatment process for a long period of time is certainly one of the reasons for pulmonary TB sufferers to experience the withdrawal of medication so that the family becomes a supporting factor for the successful treatment of family members with pulmonary TB. Many efforts have been made by the government to increase family knowledge about pulmonary tuberculosis and its treatment in the hope that the family will be able to accompany taking medication for family members with pulmonary tuberculosis. This is also the basis for the Community Service team of the Nursing Department of the Ministry of Health Kendari to increase family empowerment in accompanying patients to take medication